Elections, context, and institutions: the determinants of rent extraction in high-income democracies - Hamilton, A (2012)
Why is there significant variation in rent extraction amongst high-income democracies? A large number of political economy investigations into this research question have found that a long period of democratic rule and high per capita income are associated with less rent extraction amongst public policy-makers. However, attempts to explain the residual, yet significant, variation in rent extraction amongst countries that possess both these characteristics have been significantly more circumspect and disputed. The thesis explores how the distribution of policy-making responsibilities between electorally accountable decision-makers (EDD) and their electorally unaccountable (NEDD) public policy-making counterparts, determines the optimal level of rents extracted in any given high-income democracy context. Specifically, the thesis formally models how: (1) variation in the EDD/NEDD ratio, by altering (2) voters’ evaluation of incumbent competency, changes (3) the incentives that policy-makers, wishing to remain in office, have to minimize their short term level of rent extraction in order to signal their competency and hopefully retain office. Given these ‘career concerns’ the theoretical model predicts that an increase or decrease in the EDD/NEDD ratio will be associated with more or less rent extraction. This hypothesis is then tested empirically, primarily using an augmented version of Persson and Tabellini’s (2003) dataset. Specifically, the thesis tests whether (1) the EDD/NEDD ratio can predict variation in rent extraction only amongst high-income democracies; (2) whether voters, and not just elites, use the EDD/NEDD ratio to update their beliefs regarding the determinants of rent extraction; and (3) whether the EDD/NEDD ratio affects the level of rent extraction, once controlling for other institutional variables (Efficacy of Elections) also associated with variation in voter evaluation of incumbents’ competency. Establishing that the EDD/NEDD ratio does robustly predict variation in rent extraction is a significant finding, as it can enable analysts to predict how changes in policy-making contexts may affect the incentive for good governance in this sub-set of countries. However, the results are (1) exploratory in nature, and also (2) contingent on other factors (regime type and institutional variation), meaning that while significant, they cannot be generalized to non-democratic contexts.